Cumulative Family Risk and Cyberbullying Among Chinese Adolescents: The Chain Mediating Role of School Connectedness and Cyber Victimization - Gan, Xiong; Li, Hao; Xiang, Guo-xing; Lai, Xin-hua; Jin, Xin; Wang, Pin-yi; Zhu, Cong-shu (Frontiers in Public Health, 2022)
Abundant evidence has proved an association between cumulative family risk and adolescent cyberbullying. However, under mechanisms of this relationship were still unclear. The present study examined the mediating role of school connectedness and cyber victimization in the relation between cumulative family risk and cyberbullying. A sample of 698 Chinese adolescents was recruited to complete measures of cumulative family risk, cyberbullying, school connectedness, cyber victimization, and demographic variables. Results indicated that cumulative family risk was positively associated with cyberbullying, and this link could be mediated by school connectedness and cyber victimization. The present study identifies the potential underlying mechanism by which cumulative family risk is associated with adolescent cyberbullying, which has important implications for theory and prevention.